Peran Manajemen dalam Meningkatkan Daya Saing Koperasi Syariah dan Ritel - Maulidiyah Al Adawiyah; Dini Selasi (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2026)
Retail and sharia cooperatives play a strategic role in driving national economic growth. Cooperatives are member-based economic institutions that help expand access to capital, encourage business growth, and improve public health. However, over time, cooperatives face a number of problems. These include increasing competition from contemporary retailers, poor human resource quality, low adoption of digital technology, and suboptimal organizational governance. Facing constantly changing market dynamics, these conditions have resulted in a decline in cooperative competitiveness. Therefore, the role of management is crucial to improving operational efficiency and ensuring the sustainability of cooperative businesses. This study aims to analyze the role of management in enhancing the competitiveness of retail and sharia cooperatives through the implementation of planning, organizing, implementing, and monitoring functions. The method used in this research is a literature review, reviewing various scientific sources, such as books, journals, and relevant research reports over the past ten years. The results of the study indicate that the implementation of effective management, supported by innovation, digitalization, improved human resource quality, and good governance, can increase the competitiveness of cooperatives, making them more adaptive to changes in the business environment and community needs.